Encouraging intrinsic motivation in management training: The use of business simulation games. Issue 2 (July 2019) - Buil, Isabel; Catalán, Sara; Martínez, Eva
Abstract: Business simulation games are one of the most effective tools for motivating and engaging players actively in the learning experience. In this context, understanding which factors promote the intrinsic motivation of players is of primary importance. Self-determination theory (a theory of human motivation) postulates that contexts that support satisfaction of the three innate psychological needs for competence, autonomy, and relatedness allow individuals to maintain intrinsic motivation. However, no previous research has applied this theory to explain motivation while playing business simulation games. To address this gap, we propose that satisfaction of the needs for competence, autonomy, and relatedness influences players' intrinsic motivation, which in turn facilitates engagement. This study also explores the impact of intrinsic motivation and engagement on the development of generic skills and perceived learning. Based on a survey of 360 undergraduate business students who used a business simulation game, the findings provide support for most of the hypothesized relationships. Highlights: Business simulation games are effective tools for motivating and engaging players. Satisfaction of the psychological needs influences players' intrinsic motivation. Players' intrinsic motivation facilitates engagement with business simulation games. Intrinsic motivation and engagement facilitates the development of generic skills. Intrinsic motivation and engagement facilitates perceived learning.